Increased rates of hand ischemia following arterial cannulation in patients with severe COVID19-related pneumonia. Issue 194 (October 2020) - Dorigo, Walter; Fargion, Aaron; Paperetti, Laura; Falso, Roberto; Bonizzoli, Manuela; Fontanari, Paolo; Poggesi, Loredana; Pratesi, Carlo
Highlights: Hand ischemia following arterial cannulation is frequent among COVID19 ICU patients. It seems to be associated to the thrombotic response in the setting of the infection. Even if local outcomes are favourable, the mortality rates in such patients are high. Monitoring of the arterial accesses in ICU COVID19 in-patients is extremely important.